Hotel Guest’s Stay Prediction: A Secondary Data Approach - Ramanda Rizki Ekaputra; Andita Sari Nurmuslimah; Irvana Amelia Wendani; Raden Moch.Rafly Himiawan; Rosita Rosita (Politeknik Negeri Bandung, 2018)
Hotel guests are important in the hospitality business. Their existence affects the sustainability of the hotel. But, often the business people do not know the number of tourists who will come to their hotel. The purpose of this study is to find out what is needed by foreign or domestic tourists in hotel services, so that the businessman in the field of hospitality can step any strategy they need to do based on their target market. The research design used is a causal design. This study uses data from hotel guests in 34 provinces in Indonesia in 2016, accessed from the Badan Pusat Statistik (BPS). The analysis used is multiple regression analysis. The results of the analysis show that domestic and foreign tourists have different patterns. The number of beds positively affects domestic tourists, while the number of employees per room negatively affects domestic tourists. In contrast, the number of employees per room has a positive effect on foreign tourists staying. Similarly, the bedroom has a positive impact on foreign tourists who stay. The difference between hotel accommodation and the number of star hotel guests (domestic and foreign tourists) also occurs in a number of beds that negatively impact foreign tourists.